Sistem Penunjang Belanja Pedagang Keliling Di Lokasi Sekitar Menggunakan Haversine Berbasis Android - Richard Gozali; Liliana Liliana; Yulia Yulia (Jurnal Infra, 2021)
A traveling merchant is an effort made by a person to sellgoods/services such as vegetables, fruit, and others by travelingto places with certain routes. During this pandemic, some peoplebuy products online because people are afraid to go to placeswith large crowds. This surge in demand has made many peoplelook for sellers of vegetables and fruits. With this research, it canhelp customers to determine the location of the existence oftraveling merchants in the vicinity.By using the haversine formula, you can find out the approximatedistance between the customer and the traveling merchant.During the pandemic and the habit of staying at home, manypeople prefer to cook for themselves compared to buying. It'shard to decide which dish to cook. With the use of beautifulsoup,you can take the recipe menu of the food you want to make.From the results of the survey given to customers and travelingmerchants, it has been shown that the application is made easy touse and the survey results provide a satisfactory value. Based ontesting the distance between haversine and google maps. Theresulting haversine formula is quite accurate when compared togoogle maps. The results of the comparison of the averagedistance produced are 0.315 Km.